Phosphatidylethanolamine made in the inner mitochondrial membrane is essential for yeast cytochrome bc(1) complex function - Calzada, Elizabeth (Nat Commun, 2019)
Of the four separate PE biosynthetic pathways in eukaryotes, one occurs in the mitochondrial inner membrane (IM) and is executed by phosphatidylserine decarboxylase (Psd1). Deletion of Psd1 is lethal in mice and compromises mitochondrial function. We hypothesize that this reflects inefficient import of non-mitochondrial PE into the IM. Here, we test this by re-wiring PE metabolism in yeast by re-directing Psd1 to the outer mitochondrial membrane or the endomembrane system and show that PE can cross the IMS in both directions. Nonetheless, PE synthesis in the IM is critical for cytochrome bc(1) complex (III) function and mutations predicted to disrupt a conserved PE-binding site in the complex III subunit, Qcr7, impair complex III activity similar to PSD1 deletion. Collectively, these data challenge the current dogma of PE trafficking and demonstrate that PE made in the IM by Psd1 support the intrinsic functionality of complex III.